The farmer's perceived and expected price satisfaction on their farm products - a case study of FAMA market intervention in Selangor / Nurulahda Mad Isa - Mad Isa, Nurulahda (Faculty of Business and Management, 2006)
Federal Agricultural Marketing Authority (FAMA) was established as a statutory body in September 1965 under the Ministry of Agriculture. FAMA seeks to promote horticultural growth to meet domestic and overseas demand and to maximise farm returns through the improvement of the marketing system and development of agro- processing. The existing of FAMA's in every city in Malaysia will make the management easier to control those agriculture products and the vision of FAMA which is to be the leading authority in food and agricultural marketing will be implementing. This research tries to evaluate 'The Farmers perceived and expected price satisfaction on their farm products towards the market intervention by FAMA. The research will focus on price satisfaction of farmers from the expected and perceived performance of FAMA Selangor. There are have a 7 factors contribute to examine the result of farmers satisfaction which are, product characteristic, cost factor, demand and supply, market factor, price, negotiation and competition factor. This paper consists of five chapters, which explain the subject matter in stages. The result findings shows that majority of respondent are not achieve satisfaction towards price provided by FAMA for their farm products. So, to both parties achieve a win-win situation FAMA should make new strategies to satisfy their business customer to make the negotiation exist for the long term.